Single site laparoscopic repair of a Morgagni hernia in a pediatric patient - Amanda Muñoz; Victoria Pepper; Faraz A. Khan; Andrei Radulescu (Elsevier, 2019)
Anterior diaphragmatic hernias through the foramen of Morgagni are rare accounting for about 3% of surgically treated diaphragmatic hernias. Current management of Morgagni type diaphragmatic hernias involves surgical intervention, which is traditionally done by open laparotomy, laparoscopy or thoracoscopic approach. Here we present the case of a two year old female with a Morgagni type congenital diaphragmatic hernia (CDH) found during work-up for an upper respiratory infection, repaired using a single site laparoscopic primary approach. Keywords: Congenital diaphragmatic hernia, Single-site laparoscopic repair, Pediatric Morgagni hernia